PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PERAWATAN WAJAH KULIT DI J-KLIN BEAUTY CLINIC AND SPA JEMBER - Betty Pramudita Sari (RELASI : JURNAL EKONOMI, 2014)
Era of Globalization recent impact on a person's lifestyle, especially in matters of health and beauty skin. It is believed a very important first step for any person to perform activities. The purpose of this research was to analyze the impact of marketing mix to influence purchasing decision and costumer satisfaction of treatment of skin J-klin Beauty Clinic and Spa Jember. Data were gathered by distributing questionnaire to 108 respondents with purposive sampling method. To analysis the data, this research used Structural Equation Modelling (SEM). The result of this analysis showed that marketing mix had positive significant effect on costumer purchasing decision, marketing mix had positive significant effect on costumer satisfaction. marketing mix had positive significant effect to trust, and purchasing decision had positive significant effect on costumer satisfaction.